UJI KETERKAITAN TINGKAT PENERAPAN PHT TANAMAN PADI (Oryza Sativa L) TERHADAP FAKTOR SOSIAL PETANI (STUDI KASUS DI DUSUN BANJARDOWO KECAMATAN JOMBANG) - Isnani Khumairoh; Ambar Susanti; Canggih Nailil Maghfiroh (Program Studi Agribisnis, 2021)
There are age, education level, and duration of farmers in cultivating rice, are social factors that need to be studied to determine the extent to which these factors affect the implementation of IPM on farmers. This study aims to determine the relationship between social factors of farmers with the level of application of integrated pest control technology (IPM) in Dsn. Banjardowo district. Jombang. The research method used is descriptive analysis method, with a variable consisting of 2 variables, namely the X variable which consists of age, education and duration of farming, and 2 Y variables which consist of the application of IPM. The research population amounted to 112 respondents with a sample of 20 respondents. The questionnaire data collection technique (questionnaire) was used as a measurement with an ordinal scale or score. The factors of age, education level and duration of farming are significantly related to the level of implementation of Integrated Pest Management (IPM) in Banjardowo Hamlet, Banjardowo Village, Jombang District.